2004
DOI: 10.1080/10635150490445706
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Body Size, Cope's Rule and the Origin of Amniotes

Abstract: The evolution of body size in tetrapods is assessed using a database that includes 107 early stegocephalian species ranging in time from the Frasnian (Upper Devonian) to the Tatarian (Upper Permian). All analyses use methods that incorporate phylogenetic information (topology and branch lengths). In all tests, the impact of alternative topologies and branch lengths are assessed. Previous reports that raised doubts about the accuracy of squared-change parsimony assessment of ancestral character value appear to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
310
2
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(327 citation statements)
references
References 80 publications
8
310
2
7
Order By: Relevance
“…As we are only interested in quantifying the presence of phylogenetic signal, instead of the strength of the phylogenetic signal, we used the permutation approach developed by Laurin 46 , extended for multivariate analysis by Klingenberg and Gidaszewski 47 , and applied to shape data by other authors (for example, refs [48][49][50][51][52][53][54], to simulate the null hypothesis of complete absence of phylogenetic signal in elbow shape. The mean species shapes are randomly distributed as the tips of the phylogeny in 10,000 permutations, and for each permutation, the tree length was computed.…”
Section: Methodsmentioning
confidence: 99%
“…As we are only interested in quantifying the presence of phylogenetic signal, instead of the strength of the phylogenetic signal, we used the permutation approach developed by Laurin 46 , extended for multivariate analysis by Klingenberg and Gidaszewski 47 , and applied to shape data by other authors (for example, refs [48][49][50][51][52][53][54], to simulate the null hypothesis of complete absence of phylogenetic signal in elbow shape. The mean species shapes are randomly distributed as the tips of the phylogeny in 10,000 permutations, and for each permutation, the tree length was computed.…”
Section: Methodsmentioning
confidence: 99%
“…Extremely high measurement error could have a similar effect, but would also make us seriously doubt that the data were good enough for any sort of analysis. As discussed below, the issues of high trait lability and/or high measurement error can be addressed empirically, and recent studies have found that most traits do indeed exhibit phylogenetic signal, indicating that a star phylogeny does not provide a good fit to the data (Freckleton et al, 2002;Blomberg et al, 2003;Tieleman et al, 2003;Ackerly, 2004;Al-kahtani et al, 2004;Ashton, 2004a,b;Hutcheon and Garland, 2004;Laurin, 2004;Rezende et al, 2004;Rheindt et al, 2004;Ross et al, 2004;Muñoz-Garcia and Williams, in press). Second, it is important to consider what is meant by the 'branch lengths' of a phylogenetic tree that is used for analysis.…”
Section: Phylogeny and Modern (Statistical) Comparative Methodsmentioning
confidence: 99%
“…In such cases, it is often prudent to perform computations with more than one set of branches as a sensitivity analysis for the conclusions (e.g. see Ashton, 2004b;Hutcheon and Garland, 2004;Laurin, 2004). Similarly, some studies use multiple phylogenies (topologies) (e.g.…”
Section: Phylogeny and Modern (Statistical) Comparative Methodsmentioning
confidence: 99%
“…3) with Mesquite (Maddison and Maddison 2011). We then quantified the phylogenetic signal in elbow shape and size using a permutation test developed by Laurin (2004) for univariate traits, and extended for multivariate analyses by Klingenberg and Gidaszewski (2010), to simulate the null hypothesis of complete independence (e.g., Gidaszewski et al 2009;Figueirido et al 2010Figueirido et al , 2013Klingenberg and Marugán-Lobón 2013;Martín-Serra et al 2014a, 2014b using MorphoJ (Klingenberg 2011).…”
Section: Methodsmentioning
confidence: 99%